RuO(2) doped SnO(2) nanobipyramids on Si (100) as a field emitter - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Thin Solid Films, 2008)
Thin films of RuO(2): SnO(2) nanobipyramids have been grown on silicon (100) flat substrates, and their field emission behavior has been investigated. The field emission experiments have been performed in parallel plate configuration. In this experiment, the onset field for 0. 1 gA/ cm 2 current density has been found to be 0.2 V/mu m. The Fowler-Nordheim plot shows non-linear nature typical that of a semiconductor. The field enhancement factor has been estimated to be 35,600 cm(-1), indicating that the field emission originates from the nanometric features of the emitter. The current stability recorded at a preset value of I tA is observed to be good. Our field emission results on RuO(2): SnO(2) nanobipyramids indicate that, RuO(2): SnO(2) nanobipyramids are a potential candidate for futuristic field emission based devices. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emitter; field enhancement factor; ruthenium oxide; tin oxide

Realization of efficient field emitter based on reduced graphene oxide-Bi2S3 heterostructures - Gote, Gorkshnath H.; Bhopale, Somnath R.; More, Mahendra A.; Late, Dattatray J. (Physica Status Solidi A-Applications and Materials Science, 2019)
Herein, Bi2S3 nanorods and reduced graphene oxide (rGO)-Bi2S3 heterostructures are synthesized using a simple hydrothermal method. The structural, morphological, chemical, and elemental analysis of as-synthesized materials is performed using X-ray diffraction (XRD), Raman spectroscopy, field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Field emission (FE) studies are carried out on both pristine Bi2S3 nanorods and rGO-Bi2S3 heterostructure samples at a base pressure of approximate to 1 x 10(-8) mbar. The results show that the rGO-Bi2S3 heterostructure emitter has superior FE performance compared to pristine Bi2S3 emitters in terms of the turn-on field (2.6 V mu m(-1) at 10 mu A cm(-2)) and threshold field (4.0 V mu m(-1) at 100 mu A cm(-2)) along with a high emission current density of approximate to 1464 mu A cm(-2) at an applied electric field of 7.0 V mu m(-1). The rGO-Bi2S3 heterostructure emitter exhibits very good emission current stability, tested for more than 3 h duration, characterized by standard deviation values approximate to 2.84 and 4.06, corresponding to preset values 12 and 100 mu A. This study implies that one-step hydrothermal route can be efficiently used to synthesize organic-inorganic heterostructures that possess unique morphology. Furthermore, the synthesized rGO-Bi2S3 heterostructure emitter shows potential as an electron source for practical application in vacuum microelectronic devices.
Keywords: Bi2S3; field emission; Heterostructures; Nanorods; Reduced graphene oxide